(untitled) (Research, Society and Development, 2023)
This article reports the different ways of using ultrasound in Endodontics and how it is applied in each area, in order to make treatments increasingly qualified, quick and easy. The aim of the study is to understand how ultrasound can be applied in Endodontics and to verify its effectiveness in each treatment through literature review. After the analysis, it was observed that even ultrasound also brings disadvantages, which still stand out, being considered one of the means available that has brought more advances in ​​Endodontics, for several modalities of treatments such as root canal location, intra-radicular retainer and fractrured instruments fracture removals, root canal irrigation, removal of calcifications within the root canal, among others described in the article. This article concludes that ultrasound and its tips have become a facilitating instrument for the endodontic routine, for both the Dental Surgeon and the patient.